Application of Lean Manufacturing Principles in Increasing Factory Productivity - Eva Yuniarti Utami; Syamsu Rijal; Baso Iwang (West Science Journal Economic and Entrepreneurship, 2023)
This study looks into how a manufacturing company in Indonesia might increase factory productivity by implementing Lean Manufacturing concepts. Employing a mixed-methods approach that blends quantitative surveys and qualitative interviews, the study investigates employee awareness, adoption, and perceptions of the effects of Lean techniques. The quantitative findings show that there is a significant increase in productivity, a high degree of awareness, and partial implementation. Additional correlation analysis demonstrates a strong positive association between increases in important production metrics and the degree of Lean implementation. Qualitative results emphasize the value of cultural adaptation, implementation difficulties, and successful communication outcomes. A comprehensive conversation highlights the relationship between high awareness and implementation status, highlighting the necessity of focused training and change management. The study ends with practical suggestions for maximizing Lean tactics within businesses, emphasizing the need of cultural adaptability and viewing obstacles as chances for growth.